School Dictionary of the Slovenian Language on the Franček Web Portal - Petric Žižić, Špela (Slavistica Vilnensis, 2022)
This article presents the concept of the School Dictionary of the Slovenian Language (ŠSSJ), which is being made as part of the project Spletni portal Franček, Jezikovna svetovalnica za učitelje slovenščine in Šolski slovar slovenskega jezika (Franček Web Portal, Language Counselling for Slovenian Teachers and School Dictionary of the Slovenian Language). The School Dictionary of the Slovenian Language, which is a part of The Franček portal, the first specialized educational lexicographic-grammatic portal for Slovenian, brings a lexicographically informed, simplified display of information adapted to the abilities and knowledge of its youngest users. This article describes in greater detail the typology of explanations of nouns, verbs, adjectives and adverbs, which also includes explanations of nouns, verbs, adjectives, and adverbs’ phraseological and non-phraseological multi-word lexemes, the source for dictionary materials (together with the principles of including dictionary entries), the dictionary labels and grammatical information. Individual adjustments and simplifications are partly shown through comparison with the Dictionary of the Slovenian Standard Language (SSKJ).
Keywords: didactics; lexicography; lexicology; pedagogical language portal; explanatory dictionary; dictionary explanation